COMPARATIVE EFFECT OF PHONOPHORESIS USING IBUPROFEN AND METHYL SALICYLATE WITH ULTRASOUND USING AQUEOUS GEL IN PAIN MANAGEMENT DUE TO CERVICAL SPONDYLOSIS - Osama Saeed; Umer Shabbir; Ahmad Bilal Arif (Journal of University Medical & Dental College, 2018)
ABSTRACT: BACKGROUND: Cervical spondylosis is a general terminology used for degeneration of inter vertebral disc. Ultrasound (US) are high frequency sound waves which are generated when electrical energy is converted into mechanical vibrations by piezoelectric crystal present in ultrasound probe. Phonophoresis is a technique by which therapeutic ultrasound is used to introduce pharmacologic agents, usually anti-inﬂammatory or analgesic drugs, through intact skin into the subcutaneous tissues. OBJECTIVES: The objectives of this purposed study was to check the eﬀectiveness of ibuprofen and methyl salicylate with therapeutic ultrasound in patients with neck pain due to cervical spondylosis. The other objective was to check which treatment is best so it can improve the activities of the daily living (ADLs) of the patients. STUDY DESIGN: It was a Randomized Control Trial (Comparative Interventional Study), conducted at Madina Physical Therapy Clinical Services, Allied Hospital Faisalabad, District Headquarter Hospital (DHQ) and Aziz Fatima Hospital Faisalabad. METHODOLOGY: The participants were selected by convenient sampling technique, who were neck pain patients diagnosed with cervical spondylosis. The sample size was 80 patients divided into two groups. Group A was treatment group and received phonophoresis with ibuprofen and methyl salicylate. Group B was control and received ultrasound intervention with aqueous gel. The treatment duration was 2 months with 3 sessions per week. The pain intensity was measured by visual analogue scale (VAS) and functional level was measured neck disability index (NDI) before and after the conclusion of treatment. RESULTS: Pain mean before treatment of ibuprofen and methyl salicylate group was 7.3939±1.67592 and 7.8182±1.07397 in ultrasonic with aqueous gel group. After treatment pain mean was decreased to 1.8788±1.31714 in ibuprofen and methyl salicylate phonophoresis group and 5.0606±1.19738 in ultrasound with aqueous gel group. Functional level was also improved in ibuprofen and methyl salicylate phonophoresis group as compared to ultrasound group. CONCLUSION: It is concluded from the results that neck pain was decreased markedly of patients who received phonophoresis with ibuprofen and methyl salicylate as compared to patients who received ultrasound treatment with aqueous gel.